Reducing the primate pet trade: Actions for primatologists. Issue 1 (26th December 2019) - Norconk, Marilyn A.; Atsalis, Sylvia; Tully, Gregg; Santillán, Ana Maria; Waters, Siân; Knott, Cheryl D.; Ross, Stephen R.; Shanee, Sam; Stiles, Daniel
Abstract: This commentary emerged from a panel presentation at the International Primatological Society Congress in Nairobi, Kenya, 2018. The goal was to provide regional updates on the status of primate removal from habitat countries, especially for the pet trade, and develop guidelines that could help primatologists address this critical problem. The trade in live primates includes those used as pets, in entertainment, and as subjects of biomedical experimentation, but here we focus on those primates destined for the pet trade. Such transactions are a hugely lucrative business, impacting hundreds of thousands of individuals annually and affecting the survival of wild populations. Being intimately familiar with primate social behavior, life history and biology, primatologists, whether they work with captive or wild primates, are in a unique position to understand the nature of the trade and attempt to counter its effects. In addition to updating the status of the primate pet trade, we provide recommendations that may help primatologists formulate a plan to deal, locally and regionally, with illegal trafficking in live primates. General guidelines include increasing awareness of local customs, policies and laws; developing collaborative research opportunities for local people; engaging in training/informational opportunities; and instructing on how to take action when encountering illegally‐trafficked primates. Abstract : Research Highlights: The primate pet trade continues to grow, impacting the survival of individuals and wild populations globally. Primatologists are in a unique position to reduce the number of primates in the pet trade stream by virtue of their knowledge of primate biology and behavior, and long‐term studies in habitat countries. Actions we can take include increasing awareness of local customs and laws, increasing scientific knowledge and designing collaborative research to empower local people, and avoid posing with primates in social media posts.